The limits of argentine democracy. Readings from the draft law for The defence of democracy of 1961 - Azzolini, Nicolás (Universidad Nacional del Litoral, 2018)
In this article we work with the discussions that occurred in relation to the draft law for the defence of democracy, that was presented at the National Congress in 1961 . Despite the fact that the project sought to defend democracy against the advance of communism and other types of extremism, such discussions allow us to reconstruct the meanings linked to the concept of democracy, the differences between different anti-peronist sectors and the limits of a language based on the defense of democracy.